Systemic lupus erythematosus in Europe at the change of the millennium:Lessons from the "Euro-Lupus Cohort" - Cervera, R. (2006)
The bEuro-Lupus CohortQ is composed by 1000 patients with systemic lupus erythematosus (SLE) that have been followed prospectively since 1991. These patients have been gathered by a European consortium—the bEuro-Lupus Project GroupQ. This consortium was originated as part of the network promoted by the bEuropean Working Party on SLEQ, a working group created in 1990 in order to promote research in Europe on the different problems related to this disease. The bEuro-Lupus CohortQ provides an updated information on the SLE morbidity and mortality characteristics in the present decade as well as defines several clinical and immunological prognostic factors